Dietary supplementation with standard ileum digestible lysine in starter period improves male broiler growth weight - NASR, JAVAD; PARVIZ, MEHDI (The Indian Journal of Animal Sciences, 2015)
This research evaluates standard ileum digestible (SID) lysine density in starter period in Ross 308 male broilers to better understand the impact of increase dietary SID lysine density in live weight performance. Six diets (6 replicates) in starter period with different levels of SID lysine density, 1.411% (150% NRC), 1.321% (140% NRC), 1.215% (130% NRC), 1.126% (120% NRC), 1.035% (110% NRC) and 0.945 (100% NRC, 1994) were used in a completely randomized experimental design. All diets were iso-caloric and iso-nitrogenous. As a result of this study, Broilers fed 1.321% SID lysine level diet, body weight in 21 d was increased by 90 g compared with standard group (P<0.05). Levels of SID lysine density had a significant effect on body weight in weeks 1, 2 and 3. Feeding broilers with 1.321% SID lysine in starter diet was significant highest in body weight at 7, 14 and 21 days of age. Treatment 1.321% SID lysine was significant highest body weight gain from 0 to 7, 0 to 14 and 0 to 21 days of age and treatment 1.413% was significant highest body weight gain from 8 to 14 days of age compared with standard treatment (P<0.05). The results of this study suggest that 1.321% SID lysine density (140% NRC) in starter period diet optimized live weight and growth of Ross 308 male broiler and increasing SID lysine level from 0.945 to 1.413%, improved live weight in quadratic model.